Sorbent-based air water-harvesting systems: progress, limitation, and consideration - Asim N.; Badiei M.; Alghoul M.A.; Mohammad M.; Samsudin N.A.; Amin N.; Sopian K. (Springer Science and Business Media B.V., 2023)
Air water-harvesting systems are considered important technologies for overcoming the global water scarcity issue. Various relative humidity and cost considerations make sorbent-based air water-harvesting systems the most desirable technologies among current air water-harvesting systems. The limited availability of commercial instruments for airwater harvesting systems indicates a lack of fundamental studies on this field. In this regard, this review paper discusses and presents progress in the fields of sorbent materials and condensation and system design and future considerations in accelerating the commercialization of these technologies. Particularly, bio-inspired composition and design, mix design systems, use of renewable energy sources, modification of available sorbent materials according to functionalization, and composites are factors that require further attention. Fundamental studies of sorbent stability and life cycle, water absorbency, adsorption kinetics, heat and mass transport, regeneration condition, water-collecting surface design, and system design are essential. 2020, Springer Nature B.V.